Expanded Maternal and New Born Survival Program on Strengthening Mother and Child Health Referral System in Cilacap, Indonesia - Sulistyoningrum, Indah; Budihastuti, Uki Retno; Sutisna, Endang (Journal of Maternal and Child Health, 2016)
Background: In 2012, the maternal mortality rate or MMR and infant mortality rate or IMR in Cilacap, Central Java, tends to increase through the Expanding Maternal and Neonatal Survival or EMAS. This study aimed to determine the implementation expanding maternal and new born survival program in strengthening mother and child health and referral services.Subjects and Method: This was qualitative study. This was conducted in Cilacap.A total of 16 health professional and four societies. The informants were team leader of EMAS, EMAS quality improvement coordinator, civil society coordinator strengthener of EMAS, head of health service in Cilacap, and Chairman of the Civil Society Forum. The data was collected with interviews, observation and document and analyzed using content analysis.Results: The results of this study showed that the standard policy of the implementation of the EMAS clear, precise, clear measurable was indicators of achievement. Objectives of this study could be understood by health professionals and civil society of maternal and child health forum. Health professionals resources in an amount sufficient, with the competence and there was lack equipment and drugs in health centers. Networking system of EMAS utilization was optimal in public health center and hospitals. Communication is effective starting from the initial visit, counseling, socialization, and comparative study. Characteristics of executing agencies indicate good working procedures. Disposition implementer showed a positive attitude and support. The environmental conditions of social, political and economic support. Some of the program started in Cilacap to reduce MMR and IMR and fairly produced significant results.Conclusions: It is suggested to Cilacaphealth service to hold aid and medicine midwife training to improve skills in handling emergency cases of maternal and neonatal.Keywords: Expanding Maternal and New Born Survival, maternal mortality, infant mortalityCorrespondence: Indah Sulistyoningrum. Masters Program in Public Health, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java.Journal of Maternal and Child Health (2016), 2(1): 19-24https://doi.org/10.26911/thejmch.2016.01.01.04